The Mediating Role Of Customer Satisfaction In The Effect Of Online Customer Experience On Repurchase Intention: A Study On Tiktok Shop Users - Nirwana, Devi; Suhairi, Suhairi; Aslami, Nuri (Universitas Ibn Khladun Bogor, 2025)
This study aims to investigate the relationship between Online Customer Experience (OCE) and TikTok Shop users' Customer Satisfaction (CS) and Repurchase Intention (RI), with CS serving as a mediating variable. As social media-based e-commerce has gained popularity, especially among Indonesia's youth, TikTok Shop has emerged as a prominent online marketplace. As part of a quantitative approach, a survey was completed by 100 respondents who had made purchases on TikTok Shop over the last six months. The data was examined using multiple linear regression and mediation tests using SPSS 26. The results show that OCE has a positive and substantial impact on CS. RI is also significantly impacted by CS. However, when CS is included as a mediating variable, the direct effect of OCE on RI is minimal, indicating that CS fully mediates the relationship between customer experience and repurchase intention. These findings highlight how important it is to offer a comprehensive and satisfying user experience in order to foster customer loyalty on digital platforms. This research recommends that TikTok Shop businesses focus their strategy on enhancing customer happiness and experience quality in order to retain consumers, given the growing competition in the e-commerce industry.